India: apremier destination for outsourcing - Chorghade, Mukund S.; Chorghade, V. M.; Gurjar, Mukund K.; Ramana, Chepuri V.; Kamerkar, A. V.; Zafran, H.; Mashelkar, Raghunath Anant (Speciality Chemicals Magazine, 2005)

Geometrical solution to the sharkskin instability - Pol, Harshawardhan V.; Joshi, Yogesh M.; Tapadia, Prashant S.; Lele, Ashish K.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2007)
We study the effect of die exit divergence on the sharkskin behavior, both experimentally as well as through the use of computational fluid dynamics (CFD) simulations. Sharkskin or surface fracture is known to occur immediately after the die exit, because of the large elongational deformation that a polymer melt experiences as it exits the die. We show that the diverging taper at the die exit postpones or completely removes the occurrence of sharkskin. The corresponding CFD simulations of an equivalent K-BKZ fluid show that the taper at the die exit significantly reduces the severity of the elongational flow, thereby reducing the normal stresses as the polymer melt leaves the die. We believe that, in an extrusion operation, the provision of a diverging taper at the die exit is one of the potential measures by which sharkskin instability can be eliminated on an industrial scale.

Second world ayurveda congress (Theme: Ayurveda for the Future) - inaugural address: part I - Mashelkar, Raghunath Anant (Evidence-Based Complementary and Alternative Medicine, 2008)

Second world ayurveda congress (Theme: Ayurveda for the Future) inaugural address: part III - Mashelkar, Raghunath Anant (Evidence-Based Complementary and Alternative Medicine, 2008)

Second world ayurveda congress (Theme: Ayurveda for the Future) - inaugural address: part II - Mashelkar, Raghunath Anant (Evidence-Based Complementary and Alternative Medicine, 2008)

Fullerenol-cytotoxic conjugates for cancer chemotherapy - Chaudhuri, Padmaparna; Paraskar, Abhimanyu; Soni, Shivani; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (ACS Nano, 2009)
In the present study, we report the novel application of polyhydroxylated fullerenes (fullerenols) in cancer drug delivery. The facile synthetic procedure for generating multiple hydroxyl groups on the fullerene cage offers scope for high drug loading in addition to conferring hydrophilicity. Doxorubicin, a first line cancer chemotherapeutic, was conjugated to fullerenols through a carbamate linker, achieving ultrahigh loading efficiency. The drug-fullerenol conjugate was found to be relatively stable in phosphate buffer saline but temporally released the active drug when incubated with tumor cell lysate. The fullerenol-doxorubicin conjugate suppressed the proliferation of cancer cell-lines in vitro through a G2-M cell cycle block, resulting in apoptosis. Furthermore, in an in vivo murine tumor model, fullerenol-doxorubicin exhibited Comparable antitumor efficacy as free drug without the systemic toxicity of free doxorubicin. Additionally, we demonstrate that the fullerenol platform can be extended to other chemotherapeutic agents, such as the slightly water-soluble cisplatin, and can emerge as a new paradigm in the management of cancer.
Keywords: chemotherapy; doxorubicin; drug delivery; fullerenol; nanoparticle

Nanoparticle-mediated targeting of MAPK signaling predisposes tumor to chemotherapy - Basu, Sudipta; Harfouche, Rania; Soni, Shivani; Chimote, Geetanjali; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2009)
The MAPK signal transduction cascade is dysregulated in a majority of human tumors. Here we report that a nanoparticle-mediated targeting of this pathway can optimize cancer chemotherapy. We engineered nanoparticles from a unique hexadentate-polyD, L-lactic acid-co-glycolic acid polymer chemically conjugated to PD98059, a selective MAPK inhibitor. The nanoparticles are taken up by cancer cells through endocytosis and demonstrate sustained release of the active agent, resulting in the inhibition of phosphorylation of downstream extracellular signal regulated kinase. We demonstrate that nanoparticle-mediated targeting of MAPK inhibits the proliferation of melanoma and lung carcinoma cells and induces apoptosis in vitro. Administration of the PD98059-nanoparticles in melanoma-bearing mice inhibits tumor growth and enhances the antitumor efficacy of cisplatin chemotherapy. Our study shows the nanoparticle-mediated delivery of signal transduction inhibitors can emerge as a unique paradigm in cancer chemotherapy.
Keywords: cancer; Signal transduction

Process for the preparation of polymeric absorbents - Lele, Ashish Kishor; Varghese, Shyni; Badiger, Manohar V.; Mashelkar, Raghunath Anant (2009)
The invention discloses a process for the preparation of polymeric absorbents useful for gelling organic liquids. The process comprises mixing one or more monomers with a cross-linking agent, a free radical initiator, an optional solvent, optionally in the presence of a transition metal source and subjecting the mixture so obtained to a conventional polymerisation method. The polymer is removed, crushed to obtain polymer powder, washed with solvent and dried by conventional methods to remove unreacted monomers, followed by swelling in alcohols to obtain the desired product.

Self-similar dynamics of a flexible ring polymer in a fixed obstacle environment: a coarse-grained molecular model - Iyer, Balaji V. S.; Lele, Ashish K.; Juvekar, Vinay A.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
In this contribution we concern ourselves with an interesting problem, namely, the dynamics of ideal flexible ring polymers constrained in tin array of fixed obstacles. The fundamental issue in this problem is to understand how a topologically constrained polymer chain is able to relax its conformation in the absence of chain ends. The key physics was provided in tin elegant scaling theory by Rubinstein and co-workers (Obukhov, S. P; Rubinstein, M.; Duke, T. Dynamics of a Ring Polymer in a Gel. Phys. Rev. Lett. 1994, 73, 1263-1267). In this work we develop a coarse-grained mean-field model based oil the physical arguments of the scaling theory and derive constitutive relations for rings in fixed obstacle and melt environments. The model is composed of three distinct steps. In the first step the dynamics of an arbitrary section of a ring chain is worked out based oil fractal Blob-Spring (BS) dynamics, and the center of mass diffusion and the relaxation spectrum of this section are determined. In the second step the center of mass diffusion obtained using the BS dynamics is used to model the one-dimensional diffusion of the section in a topologically constrained environment. In the final step we invoke the idea of dynamic self-similarity and argue that the dynamics described in the first and the second step, for any arbitrary section of the chain, applies to all sections of the chain. The constitutive relation is obtained consequently as the superposition of dynamic response of all sections of the ring chain.

Some mechanistic insights into the gelation of regenerated silk fibroin sol - Nagarkar, Shailesh; Patil, Avinash; Lele, Ashish K.; Bhat, Suresh K.; Bellare, Jayesh R.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
We provide some new insights into the kinetics and mechanism of sol-gel transition as it pertains to regenerated silk fibroin, which is the principle structural protein of silkworm silk fiber. Silk fibroin was dissolved in lithium bromide and dialyzed against deionized water to prepare a regenerated fibroin solution. This solution was found to be unstable at lower pH and transformed into a colloidal gel. The kinetics and mechanism of the sol-gel transition were investigated using rheology and light scattering. We show that gelation proceeds in two steps. In the first step, a weak gel is formed almost immediately upon lowering the pH, while in the second step further gelation proceeds rapidly after a long induction time to form a self-similar structure.

Traditional medicine-inspired approaches to drug discovery: can ayurveda show the way forward? - Patwardhan, Bhushan; Mashelkar, Raghunath Anant (Drug Discovery Today, 2009)
Drug discovery strategies based on natural products and traditional medicines are re-emerging as attractive options. We suggest that drug discovery and development need not always be confined to new molecular entities. Rationally designed, carefully standardized, synergistic traditional herbal formulations and botanical drug products with robust scientific evidence can also be alternatives. A reverse pharmacology approach, inspired by traditional medicine and Ayurveda, can offer a smart strategy for new drug candidates to facilitate discovery process and also for the development of rational synergistic botanical formulations.

Beyond irreverence - Mashelkar, Raghunath Anant (Current Science, 2010)

Coupling growth-factor engineering with nanotechnology for therapeutic angiogenesis - Roy, Rituparna Sinha; Soni, Shivani; Harfouche, Rania; Vasudevan, Pooja R.; Holmes, Oliver; de Jonge, Hugo; Rowe, Arthur; Paraskar, Abhimanyu; Hentschel, Dirk M.; Chirgadze, Dimitri; Blundell, Tom L.; Gherardi, Ermanno; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Therapeutic angiogenesis is an emerging paradigm for the management of ischemic pathologies. Proangiogenic Therapy is limited, however, by the current inability to deliver angiogenic factors in a sustained manner at the site of pathology. In this study, we investigated a unique nonglycosylated active fragment of hepatocyte growth factor/scatter factor, 1K1, which acts as a potent angiogenic agent in vitro and in a zebrafish embryo and a murine matrigel implant model. Furthermore, we demonstrate that nanoformulating 1K1 for sustained release temporally alters downstream signaling through the mitogen activated protein kinase pathway, and amplifies the angiogenic outcome. Merging protein engineering and nanotechnology offers exciting possibilities for the treatment of ischemic disease, and furthermore allows the selective targeting of downstream signaling pathways, which translates into discrete phenotypes.
Keywords: cardiovascular disease; HGF/SF; ischemic disease; nanoparticle; protein engineering

Harnessing structure-activity relationship to engineer a cisplatin nanoparticle for enhanced antitumor efficacy - Paraskar, Abhimanyu S.; Soni, Shivani; Chin, Kenneth T.; Chaudhuri, Padmaparna; Muto, Katherine W.; Berkowitz, Julia; Handlogten, Michael W.; Alves, Nathan J.; Bilgicer, Basar; Dinulescu, Daniela M.; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cisplatin is a first line chemotherapy for most types of cancer. However, its use is dose-limited due to severe nephrotoxicity. Here we report the rational engineering of a novel nanoplatinate inspired by the mechanisms underlying cisplatin bioactivation. We engineered a novel polymer, glucosamine-functionalized polyisobutylene-maleic acid, where platinum (Pt) can be complexed to the monomeric units using a monocarboxylato and an O –> Pt coordinate bond. We show that at a unique platinum to polymer ratio, this complex self-assembles into a nanoparticle, which releases cisplatin in a pH-dependent manner. The nanoparticles are rapidly internalized into the endolysosomal compartment of cancer cells, and exhibit an IC50 (4.25 + 0.16 mu M) comparable to that of free cisplatin (3.87 +/- 0.37 mu M), and superior to carboplatin (14.75 +/- 0.38 mu M). The nanoparticles exhibited significantly improved antitumor efficacy in terms of tumor growth delay in breast and lung cancers and tumor regression in a K-ras(LSL/+)/Pten(fl/fl) ovarian cancer model. Furthermore, the nanoparticle treatment resulted in reduced systemic and nephrotoxicity, validated by decreased biodistribution of platinum to the kidney as quantified using inductively coupled plasma spectroscopy. Given the universal need for a better platinate, we anticipate this coupling of nanotechnology and structure-activity relationship to rationally reengineer cisplatin could have a major impact globally in the clinical treatment of cancer.
Keywords: cancer; chemotherapy; nanomedicine

Irreverence and Indian science - Mashelkar, Raghunath Anant (Science, 2010)

Cholesterol-tethered platinum II-based supramolecular nanoparticle increases antitumor efficacy and reduces nephrotoxicity - Sengupta, Poulomi; Basu, Sudipta; Soni, Shivani; Pandey, Ambarish; Roy, Bhaskar; Oh, Michael S.; Chin, Kenneth T.; Paraskar, Abhimanyu S.; Sarangi, Sasmit; Connor, Yamicia; Sabbisetti, Venkata S.; Kopparam, Jawahar; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Nanoscale drug delivery vehicles have been harnessed extensively as carriers for cancer chemotherapeutics. However, traditional pharmaceutical approaches for nanoformulation have been a challenge with molecules that exhibit incompatible physicochemical properties, such as platinum-based chemotherapeutics. Here we propose a paradigm based on rational design of active molecules that facilitate supramolecular assembly in the nanoscale dimension. Using cisplatin as a template, we describe the synthesis of a unique platinum (II) tethered to a cholesterol backbone via a unique monocarboxylato and O -> Pt coordination environment that facilitates nanoparticle assembly with a fixed ratio of phosphatidylcholine and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine- N-[amino (polyethylene glycol)-2000]. The nanoparticles formed exhibit lower IC50 values compared with carboplatin or cisplatin in vitro, and are active in cisplatin-resistant conditions. Additionally, the nanoparticles exhibit significantly enhanced in vivo antitumor efficacy in murine 4T1 breast cancer and in K-Ras(LSL/+/)Pten(fl/fl) ovarian cancer models with decreased systemic- and nephro-toxicity. Our results indicate that integrating rational drug design and supramolecular nanochemistry can emerge as a powerful strategy for drug development. Furthermore, given that platinum-based chemotherapeutics form the frontline therapy for a broad range of cancers, the increased efficacy and toxicity profile indicate the constructed nanostructure could translate into a nextgeneration platinum-based agent in the clinics.
Keywords: chemotherapy; nanomedicine

India's science for all academy - Mashelkar, Raghunath Anant (Science, 2012)

Rapid self-healing hydrogels - Phadke, Ameya; Zhang, Chao; Arman, Bedri; Hsu, Cheng-Chih; Mashelkar, Raghunath Anant; Lele, Ashish K.; Tauber, Michael J.; Arya, Gaurav; Varghese, Shyni (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Synthetic materials that are capable of autonomous healing upon damage are being developed at a rapid pace because of their many potential applications. Despite these advancements, achieving self-healing in permanently cross-linked hydrogels has remained elusive because of the presence of water and irreversible cross-links. Here, we demonstrate that permanently cross-linked hydrogels can be engineered to exhibit self-healing in an aqueous environment. We achieve this feature by arming the hydrogel network with flexible-pendant side chains carrying an optimal balance of hydrophilic and hydrophobic moieties that allows the side chains to mediate hydrogen bonds across the hydrogel interfaces with minimal steric hindrance and hydrophobic collapse. The self-healing reported here is rapid, occurring within seconds of the insertion of a crack into the hydrogel or juxtaposition of two separate hydrogel pieces. The healing is reversible and can be switched on and off via changes in pH, allowing external control over the healing process. Moreover, the hydrogels can sustain multiple cycles of healing and separation without compromising their mechanical properties and healing kinetics. Beyond revealing how secondary interactions could be harnessed to introduce new functions to chemically crosslinked polymeric systems, we also demonstrate various potential applications of such easy-to-synthesize, smart, self-healing hydrogels.
Keywords: adhesives; biomimetic materials; Hydrophobicity; molecular dynamics; smart materials

Supramolecular nanoparticles that target phosphoinositide-3-kinase overcome insulin resistance and exert pronounced antitumor efficacy - Kulkarni, Ashish A.; Roy, Bhaskar; Rao, Poornima S.; Wyant, Gregory A.; Mahmoud, Ayaat; Ramachandran, Madhumitha; Sengupta, Poulomi; Goldman, Aaron; Kotamraju, Venkata Ramana; Basu, Sudipta; Mashelkar, Raghunath Anant; Ruoslahti, Erkki; et al. (Cancer Research, 2013)
The centrality of phosphoinositide-3-kinase (PI3K) in cancer etiology is well established, but clinical translation of PI3K inhibitors has been limited by feedback signaling, suboptimal intratumoral concentration, and an insulin resistance ``class effect.'' This study was designed to explore the use of supramolecular nanochemistry for targeting PI3K to enhance antitumor efficacy and potentially overcome these limitations. PI3K inhibitor structures were rationally modified using a cholesterol-based derivative, facilitating supramolecular nanoassembly with L-alpha-phosphatidylcholine and DSPE-PEG [1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polythylen e glycol)]. The supramolecular nanoparticles (SNP) that were assembled were physicochemically characterized and functionally evaluated in vitro. Antitumor efficacy was quantified in vivo using 4T1 breast cancer and K-Ras(LSL/+)/Pten(fl/fl) ovarian cancer models, with effects on glucose homeostasis evaluated using an insulin sensitivity test. The use of PI103 and PI828 as surrogate molecules to engineer the SNPs highlighted the need to keep design principles in perspective; specifically, potency of the active molecule and the linker chemistry were critical principles for efficacy, similar to antibody-drug conjugates. We found that the SNPs exerted a temporally sustained inhibition of phosphorylation of Akt, mTOR, S6K, and 4EBP in vivo. These effects were associated with increased antitumor efficacy and survival as compared with PI103 and PI828. Efficacy was further increased by decorating the nanoparticle surface with tumor-homing peptides. Notably, the use of SNPs abrogated the insulin resistance that has been associated widely with other PI3K inhibitors. This study provides a preclinical foundation for the use of supramolecular nanochemistry to overcome current challenges associated with PI3K inhibitors, offering a paradigm for extension to other molecularly targeted therapeutics being explored for cancer treatment. (C)2013 AACR.

What will it take for Indian science, technology and innovation to make global impact? - Mashelkar, Raghunath Anant (Current Science, 2015)

Reporter nanoparticle that monitors its anticancer efficacy in real time - Kulkarni, Ashish; Rao, Poornima; Natarajan, Siva; Goldman, Aaron; Sabbisetti, Venkata S.; Khater, Yashika; Korimerla, Navya; Chandrasekar, Vineethkrishna; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The ability to monitor the efficacy of an anticancer treatment in real time can have a critical effect on the outcome. Currently, clinical readouts of efficacy rely on indirect or anatomic measurements, which occur over prolonged time scales postchemotherapy or postimmunotherapy and may not be concordant with the actual effect. Here we describe the biology-inspired engineering of a simple 2-in-1 reporter nanoparticle that not only delivers a cytotoxic or an immunotherapy payload to the tumor but also reports back on the efficacy in real time. The reporter nanoparticles are engineered from a novel two-staged stimuli-responsive polymeric material with an optimal ratio of an enzyme-cleavable drug or immunotherapy (effector elements) and a drug function-activatable reporter element. The spatiotemporally constrained delivery of the effector and the reporter elements in a single nanoparticle produces maximum signal enhancement due to the availability of the reporter element in the same cell as the drug, thereby effectively capturing the temporal apoptosis process. Using chemotherapy-sensitive and chemotherapy-resistant tumors in vivo, we show that the reporter nanoparticles can provide a real-time noninvasive readout of tumor response to chemotherapy. The reporter nanoparticle can also monitor the efficacy of immune checkpoint inhibition in melanoma. The self-reporting capability, for the first time to our knowledge, captures an anticancer nanoparticle in action in vivo.
Keywords: chemotherapy; immunotherapy; monitoring; nanoparticle; reporter

Impact of science, technology and innovation on the economic and political power - Mashelkar, Raghunath Anant (AI & Society, 2017)

architecturally rational hemostat for rapid stopping of massive bleeding on anticoagulation therapy - Lee, Vivian K.; Lee, Taewoo; Ghosh, Amrit; Saha, Tanmoy; Bais, V. Manish; Bharani, Kala Kumar; Chag, Milan; Parikh, Keyur; Bhatt, Parloop; Namgung, Bumseok; Venkataramanan, Geethapriya; Agrawal, Animesh; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Hemostatic devices are critical for managing emergent severe bleeding. With the increased use of anticoagulant therapy, there is a need for next- generation hemostats. We rationalized that a hemostat with an architecture designed to increase contact with blood, and engineered from a material that activates a distinct and undrugged coagulation pathway can address the emerging need. Inspired by lung alveolar architecture, here, we describe the engineering of a next- generation single - phase chitosan hemostat with a tortuous spherical microporous design that enables rapid blood absorption and concentrated platelets and fibrin microthrombi in localized regions, a phenomenon less observed with other classical hemostats without structural optimization. The interaction between blood components and the porous hemostat was further amplified based on the charged surface of chitosan. Contrary to the dogma that chitosan does not directly affect physiological clotting mechanism, the hemostat induced coagulation via a direct activation of platelet Toll - like receptor 2. Our engineered porous hemostat effectively stopped the bleeding from murine liver wounds, swine liver and carotid artery injuries, and the human radial artery puncture site within a few minutes with significantly reduced blood loss, even under the anticoagulant treatment. The integration of engineering design principles with an understanding of the molecular mechanisms can lead to hemostats with improved functions to address emerging medical needs.
Keywords: biomaterial; clotting; hemostasis; hemostat; trauma